Characteristics overview of mother with perinatal death at Dr. Soetomo Hospital in 2015 - Yulisa Haslinda; Budi Prasetyo (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to determine the frequency distribution of perinatal mortality and maternal characteristic features in terms of age, parity, gestational age and pregnancy complications in Dr.Soetomo Hospital Surabaya in 2015. Materials and Methods: A descriptive study conducted by collecting data on patients who experienced perinatal mortality of infants born from January to December 2015 in Dr. Soetomo, Hospital Surabaya. Samples were collected using total sampling. The samples must meet the following criteria: mothers of infants with perinatal mortality in Dr. Soetomo Hospital, Surabaya, from January to December 2015.Results: There were 206 perinatal deaths out of 1018 births in Dr. Soetomo during 2015, of which 58% was live birth and 42% was stillbirth. Most of perinatal mortality found in the preterm gestational age as much as 78%, and gestational age 28-<37 weeks (58%). Most of perinatal mortality occured in infants with less than 1500 grams birth weight, which was as much as 53% of all perinatal deaths and infant whose birth weight from1500 to 2500 grams was about 29%. Most perinatal mortality found in multigravida (54%) and in infants whose mothers experienced preeclampsia in pregnancy complications (35%), followed by infant mortality in women with non-obstetric complications (23%).Conclusion: Perinatal mortality in Dr. Soetomo Hospital was mostly found in multigravida mothers, 16-35 years old maternal age, 28-37 weeks gestational age and those with complications of preeclampsia.